2009
DOI: 10.1128/jvi.02271-08
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Cell Leukemia Virus Type 2 Rex Carboxy Terminus Is an Inhibitory/Stability Domain That Regulates Rex Functional Activity and Viral Replication

Abstract: Human T-cell leukemia virus (HTLV) regulatory protein, Rex, functions to increase the expression of the viral structural and enzymatic gene products. The phosphorylation of two serine residues (S151 and S153) at the C terminus is important for the function of HTLV-2 Rex (Rex-2). The Rex-2 phosphomimetic double mutant (S151D, S153D) is locked in a functionally active conformation. Since rex and tax genes overlap, Rex S151D and S153D mutants were found to alter the Tax oncoprotein coding sequence and transactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 55 publications
(56 reference statements)
0
19
1
Order By: Relevance
“…Moreover, we recently reported that the carboxy terminus of Rex-2 contains a stability/inhibitory domain that is positively regulated through phosphorylation (54). However, a complete map of site-specific phosphorylation of Rex-2 is lacking, and the precise role it plays in protein function remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, we recently reported that the carboxy terminus of Rex-2 contains a stability/inhibitory domain that is positively regulated through phosphorylation (54). However, a complete map of site-specific phosphorylation of Rex-2 is lacking, and the precise role it plays in protein function remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…1). In addition to the nuclear localization signal/RBD, central core activation domain/nuclear export signal, and multimerization domains that were also shared with the functionally homologous HTLV-1 Rex (32), we also reported that Rex-2 contained a unique C-terminal inhibitory/stability domain that was found to be important for proper nucleocytoplasmic shuttling, subcellular localization, and function (32,54). This domain also encompasses at least one phosphorylated serine residue (S151), identified by substitutional mutational and peptide phosphoamino acid analysis, that is critical for Rex-2 function in vivo (31,32).…”
Section: Functional Domains Of Htlv-2 Rex Two Species Of Rex-2 (P24mentioning
confidence: 99%
See 2 more Smart Citations
“…The authors mapped also HTLV-2 Rex and found that phosphorylations on Thr-164, Ser-151 and Ser-153 are functional [136] . In particular, Ser-151 phosphorylation correlates with Rex nuclear/nucleolar localization [136] and with an active Rex protein [137] . For unknown reasons, Rex expression promotes the expression of the Src kinase FynB, usually absent in T cells, thus altering the TCR pathway [41] .…”
Section: Htlv-1 Rex Phosphorylation and Tcr Pathwaymentioning
confidence: 98%